Assessment of Indonesian Banking Stock Performance Using the Multi-Index Approach 2018-2022 - Laksana, Reksha; Wardini, Anggi Putri Kusuma; Gustirani, Indri (ADPEBI International Journal of Business and Social Science, 2025)
company stocks on Indonesia Stock Exchange (IDX) in the period 2018 to 2022. Methodology/approach – It is a quantitative descriptive research and the sampling method used purposive sampling. Over the observation period, 2220 monthly closing data points were collected from 37 banking company stocks as a sample. Findings – The research results indicate based on the Sharpe Index, ARTO and BNLI exhibit the best performance. According to the Treynor Index, BMRI show the best performance, while the Jensen Index highlights BBHI as having the best performance. Novelty/value – These findings can be valuable for investors in making informed decisions regarding their investments in banking companies on Indonesian Stock Exchange.